2012
DOI: 10.1371/journal.ppat.1003059
|View full text |Cite
|
Sign up to set email alerts
|

Species-Specific Inhibition of RIG-I Ubiquitination and IFN Induction by the Influenza A Virus NS1 Protein

Abstract: Influenza A viruses can adapt to new host species, leading to the emergence of novel pathogenic strains. There is evidence that highly pathogenic viruses encode for non-structural 1 (NS1) proteins that are more efficient in suppressing the host immune response. The NS1 protein inhibits type-I interferon (IFN) production partly by blocking the TRIM25 ubiquitin E3 ligase-mediated Lys63-linked ubiquitination of the viral RNA sensor RIG-I, required for its optimal downstream signaling. In order to understand possi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
312
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 282 publications
(326 citation statements)
references
References 51 publications
7
312
0
1
Order By: Relevance
“…In such an arrangement, RING dimerization could potentially be enhanced by substrate binding, thereby ensuring that TRIM25 activity is only available in the correct setting. This is particularly interesting in the light of the observation that viral proteins such as NS1 bind to the coiled‐coil region of TRIM25, which could prevent intramolecular RING dimerization in this model and hence activity (Gack et al , 2009; Rajsbaum et al , 2012). In contrast, in TRIM32 the RING acts as an independent dimerization module and promotes formation of a TRIM tetramer, in which the RING dimers are located on either side of the central coiled‐coil (Figs 7 and EV4).…”
Section: Discussionmentioning
confidence: 99%
“…In such an arrangement, RING dimerization could potentially be enhanced by substrate binding, thereby ensuring that TRIM25 activity is only available in the correct setting. This is particularly interesting in the light of the observation that viral proteins such as NS1 bind to the coiled‐coil region of TRIM25, which could prevent intramolecular RING dimerization in this model and hence activity (Gack et al , 2009; Rajsbaum et al , 2012). In contrast, in TRIM32 the RING acts as an independent dimerization module and promotes formation of a TRIM tetramer, in which the RING dimers are located on either side of the central coiled‐coil (Figs 7 and EV4).…”
Section: Discussionmentioning
confidence: 99%
“…The sialic acid specificity of different viruses has been suggested to explain why some viruses appear to be more lethal than others [5, 73,75]. [41,42] It also induces the downregulation of the IFN-α receptor [43] and upregulates inhibitors of JAK/STAT signalling (SOCS1 and SOCS3) [43,44] During infection, non-structural protein-1 also blocks pro-apoptotic signalling by protein kinase R [45,46] and prevents the activation of NF-κB [47] Nonstructural protein-2 Expressed during replication, not part of the mature virion…”
Section: Molecular and Cellular Interactions At The Virus-host Interfacementioning
confidence: 99%
“…This suggests that only waterfowl-derived RIG-Is are functional in chicken DF-1 cells and some factors necessary for mammal-derived RIG-I activation are missing or unrecognizable in chicken cells. For example, RIPLET, which ubiquitinates Lys849 and Lys851 in the C-terminal domain of RIG-I (Gao et al, 2009;Oshiumi et al, 2009Oshiumi et al, , 2010, is absent from chicken and duck genomes (Magor et al, 2013;Rajsbaum et al, 2012).…”
Section: Ifn-bmentioning
confidence: 99%
“…2a-f). Another study reported that only avian influenza virus-derived NS1 can bind to chicken TRIM25, thereby suppressing the induction of IFN (Rajsbaum et al, 2012). Mouse-adapted IAV NS1 specifically binds to mouse RIPLET in mouse cells (Rajsbaum et al, 2012).…”
Section: Ifn-bmentioning
confidence: 99%